Persiapan Uji Kompetensi Peserta Program Profesi Guru (UKPPPG) bagi Guru Otomotif pada MGMP Teknik Otomotif Sumatera Barat untuk Meningkatkan Profesionalisme dan Kompetensi - Nuzul - Hidayat; Wawan Purwanto; Toto Sugiarto (PAKAR Pendidikan, 2026)
The Competency Test for Teacher Professional Education Program Participants (UKPPPG) is an essential stage for assessing the professionalism of vocational teachers, including those in the field of automotive engineering. Adequate preparation is required to ensure that teachers meet competency standards while also improving the quality of learning in vocational schools. This study aims to describe the preparation strategies facilitated by the Automotive Engineering Subject Teacher Forum (MGMP) in West Sumatra and to identify the challenges teachers face in preparing for the UKPPPG. This research employed a descriptive qualitative approach with a case study design. The subjects consisted of 15 automotive teachers who were actively involved in MGMP activities and preparing for the UKPPPG. Data were collected through in-depth interviews, participatory observation, and document analysis. Thematic analysis was carried out through coding, theme identification, and verification using source and method triangulation. The findings indicate that MGMP preparation strategies include lesson plan development, microteaching, and exam discussions. These activities improved teachers’ pedagogical skills; however, limitations such as inadequate workshop facilities, conventional teaching materials, and the lack of computer-based simulations hindered optimal preparation. This study concludes that MGMP plays a significant role in preparing teachers for the UKPPPG, although its effectiveness remains limited to pedagogical aspects. A more comprehensive strategy involving curriculum renewal, access to updated materials, psychological support, and digital technology integration is needed.